2021
DOI: 10.1186/s13075-021-02456-4
|View full text |Cite
|
Sign up to set email alerts
|

Positive feedback regulation between USP15 and ERK2 inhibits osteoarthritis progression through TGF-β/SMAD2 signaling

Abstract: Background The transforming growth factor-β (TGF-β) signaling pathway plays an essential role in maintaining homeostasis in joints affected by osteoarthritis (OA). However, the specific mechanism of non-SMAD and classical SMAD signaling interactions is still unclear, which needs to be further explored. Methods In ATDC5 cells, USP15 overexpression and knockout were performed using the transfected lentivirus USP15 and Crispr/Cas9. Western blotting an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Similarly, differential expression of AP-1 signaling pathway components including Mapk1 (ERK2), Map3k8 (MEKK8) and Junb (AP1) is also expected to contribute to large-scale cellular and molecular changes. Regarding ERK2, Wang et al reported that overexpression of this kinase was involved in maintaining cartilage homeostasis through modulating the TGF-b/SMAD axis via reducing the expression of Col2a1, Aggrecan, and Sox9, which are key molecules for cartilage homeostasis (30). The AP-1 subunit, JunB, has been proposed as a negative regulator of proliferation and production of cytokines in fibroblasts (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, differential expression of AP-1 signaling pathway components including Mapk1 (ERK2), Map3k8 (MEKK8) and Junb (AP1) is also expected to contribute to large-scale cellular and molecular changes. Regarding ERK2, Wang et al reported that overexpression of this kinase was involved in maintaining cartilage homeostasis through modulating the TGF-b/SMAD axis via reducing the expression of Col2a1, Aggrecan, and Sox9, which are key molecules for cartilage homeostasis (30). The AP-1 subunit, JunB, has been proposed as a negative regulator of proliferation and production of cytokines in fibroblasts (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al indicated that overexpression of MAPK1 reduced the inhibitory effect of miR-320c on articular chondrocyte proliferation and attenuated the promoting effect of miR-320c on apoptosis ( Zhao et al, 2021 ). Wang et al observed that the positive feedback regulation between ERK2 (MAPK1) and USP15 played a critical role in the regulation of TGF-β/SMAD2 signaling and the maintaining of cartilage phenotype ( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… 299 USP15 also inhibits OA progression by deubiquitinating ERK2 and enhancing ERK2-induced TGF-β/SMAD2 signaling. 300 …”
Section: Regulation Of Tgf-β and Bmp Signaling In Bonementioning
confidence: 99%